Management of Nutrition in Gastric Emptying Preparation before Medical Procedures - Stella Evangeline Bela; Ari Fahrial Syam; Luciana Budiati Sutanto (The Indonesian Society for Digestive Endoscopy, 2012)
Patient preparation before medical procedures, for example in elective surgery, abdominal ultrasonograhy (USG), endoscopy, intubation, etc., is by emptying the stomach. Attempt in emptying stomach is by fasting since the night before medical procedure with the intention to decrease the risk of aspiration. Management of nutrition guidelines in preparation of medical procedures currently refers to pre- surgery fasting which is recommended by American Society of Anaesthesiologist (ASA) and the Canadian Anaesthetists Society (CAS). In Indonesia, pre-surgery fasting guideline is suggested by Indonesia Society of Anesthesiology and Intensive Care. However, in various unit of service, fasting the patient since the night before is still performed. Development of nutrition management in medical procedures has experienced many changes, such as surgery which is aimed to restore organ normal function and to accelerate the healing of patients. Various studies on nutrition are developed in conjunction with the programs development to optimize pre-surgery preparation. Keywords: nutrition management, pre-surgery nutrition, aspiration